Oxford new syllabus primary mathematic workbook 5B(2nd edition) - Yee, Dr Foong Pui (Oxford University Press Pakistan, 2007)
ew Syllabus Primary Mathematics (NSPM) is a series of textbooks and workbooks specially written to reflect a student-centred approach, which serves to engage pupils so that they have a solid foundation in Mathematics. This series meets the objectives of Pakistan Single National Curriculum 2020. New syllabus Primary Mathematics (NSPM) is a comprehensive series which adopts a spiral design with carefully built-up mathematical concepts and processes. The Concrete-Pictorial-Abstract approach forms an integral part of the learning process through the materials developed for this series. NSPM incorporates the use of concrete aids and manipulatives, use of information and communications technology (ICT), problem-solving, and group work.